Peningkatan Kualitas Pendidikan Melalui Partisipasi Masyarakat di SMP YPPSB Sangatta - Siti Asiah; Miftahul Jannah; Muhammad Yasin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
Community participation is an activity or matter of taking part in activities in an organization. Community participation in education is very necessary and important because it greatly influences the development of the quality of the school or education. Therefore, community participation becomes an important component to be developed and empowered in education. This research contains an explanation of forms of community participation, factors that can increase community participation and forms of community participation that can improve the quality of education at YPPSB Sangatta Middle School. This research aims to increase public understanding and awareness so that they participate in education. This article was created in the form of a qualitative method through interviews, documentation and observations which were then arranged according to critical analysis so that appropriate data was obtained. The results of the research include an explanation of community participation in education, including the forms and factors that influence the level of participation, whether supporting or hindering, in addition to obtaining data regarding efforts made by the community which have a positive impact on both the school and the community itself.